Tropical Spiderwort (Commelina benghalensis L.), Identification and Control - Jason A. Ferrell; Gregory E. MacDonald; Barry J. Brecht (EDIS, 2004)
Tropical spiderwort is an aggressive weed that produces aerial (above ground) and subterranean (below ground) flowers. This results in viable seed being produced both above and below ground. Tropical spiderwort also possesses the ability to root at the nodes and can be propagated from cut stems. Therefore, light cultivation can often break plant parts and increase the area of infestation. Although tropical spiderwort is difficult to control, early identification and proactive management can greatly reduce its impact on crop yields. This document is SS-AGR-223, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published May 2004.